PELATIHAN CABUT DURI IKAN PADA KELOMPOK USAHA DESA BABULU LAUT KABUPATEN PENAJAM PASER UTARA - Widya Kusumaningrum; Ristiana Eryati; Doni Darmasetiadi; Etik Sulistiowati Ningsih; Andi Mismawati; Rani Novia; Samsul Rizal; Jurianto Muhammad Nur (LPPM Institut Pendidikan Nusantara Global, 2026)
Desa Babulu Laut is a coastal village located in Kecamatan Babulu, Kabupaten Penajam Paser Utara, Kalimantan Timur. The village has significant fisheries potential, with milkfish (Chanos chanos) as its main catch. However, this potential has not been optimally utilized, as most of the catch is still sold in fresh form without further processing. This condition results in relatively low economic value and has not significantly contributed to improving the community’s income. This activity aims to increase the added value of milkfish through proper and hygienic processing training. The methods used include field observation, problem identification, and training for community participants. The training was conducted through lectures, demonstrations, and hands-on practice, particularly focusing on hygienic milkfish deboning techniques and simple yet economical and attractive packaging methods. The results of this activity indicate an improvement in the community’s knowledge and skills in processing milkfish into higher-value products. In addition, participants gained a better understanding of the importance of product quality and packaging in attracting consumers and enhancing competitiveness in the market.